The role of psychological capital and career success in marital adjustment - Mohammadi, Nasrin; Darbani, Seyed Ali; Parsakia, Kamdin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: Career success as the main factor in the health and well-being of employees and a prelude to the occurrence of desirable personal and organizational career outcomes has received the attention of the field of organizational psychology. Therefore, the present study investigated the role of psychological capital and career success in marital adjustment in married students. Methodology: This research is a correlational descriptive method. The statistical population of this research was all employed and married students of Azad University, South Tehran branch, who were studying at this university in the second semester of the 2020-2021 academic year. The sample size was 200 people. They were selected by the available sampling method (voluntarily). Spiner’s (1976) Marital Adjustment Questionnaire, Luthans and Olive’s Psychological Capital Questionnaire (2007), and Nabi’s Career Success Questionnaire (2001) were used to measure the research variables. The linear regression analysis method was used with the help of SPSS software to analyze the research data. Results: The findings indicated that among the components of psychological capital, optimism, hope, and resilience have a significant and direct relationship with marital adjustment. Also, among the variable components of career success, the subjective success component has a significant and direct relationship with marital adjustment. Conclusion: The results showed that psychological capital and job success are effective in the marital adjustment of married students.